2022
DOI: 10.1161/circheartfailure.122.009844
|View full text |Cite
|
Sign up to set email alerts
|

Early Outcomes of Heart Transplantation Using Donation After Circulatory Death Donors in the United States

Abstract: Background: Limited donor availability and evolution in procurement techniques have renewed interest in heart transplantation (HT) with donation after circulatory death (DCD). The aim of this study is to evaluate outcomes of HT using DCD in the United States. Methods: The United Network for Organ Sharing registry was used to identify adult HT recipients from 2019 to 2021. Recipients were stratified between DCD and donation after brain death. Propensity-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…31,[38][39][40] However, NRP is increasingly used in DCD heart and abdominal organ procurements in the United States and has shown favorable utilization and graft outcomes for both kidney and liver transplantations compared with static cold storage. 13,41,42 NRP was also found to be safe for DCD lung retrieval in a large institutional series. 43 While no studies have demonstrated the superiority of NRP over EVP for DCD heart transplantation, this procurement strategy for DCD hearts is associated with improved utilization and posttransplant outcomes for concomitantly procured abdominal organs.…”
Section: Discussionmentioning
confidence: 74%
See 2 more Smart Citations
“…31,[38][39][40] However, NRP is increasingly used in DCD heart and abdominal organ procurements in the United States and has shown favorable utilization and graft outcomes for both kidney and liver transplantations compared with static cold storage. 13,41,42 NRP was also found to be safe for DCD lung retrieval in a large institutional series. 43 While no studies have demonstrated the superiority of NRP over EVP for DCD heart transplantation, this procurement strategy for DCD hearts is associated with improved utilization and posttransplant outcomes for concomitantly procured abdominal organs.…”
Section: Discussionmentioning
confidence: 74%
“…Moreover, encouraging international outcomes with DCD heart transplantation has spurred the utilization of these organs by almost one-fifth of US centers since 2019. 13 This analysis summarized waitlist and transplant outcomes with DCD kidney, liver, lung, and heart transplantation in the United States.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Success rates in heart transplantation after DCDD are improving rapidly. 36 Last, one might suggest that our proposal is arbitrary. Why not just declare someone dead when they have permanently lost consciousness?…”
Section: Potential Counterargumentsmentioning
confidence: 99%
“…[1][2][3] The opioid epidemic has led to an expanded donor pool, 4 and additional expansion has occurred with the development of protocols for the use of hepatitis C positive organs 5 and donation after cardiac death (DCD) hearts. 6 Yet, organ preservation still remains a major issue limiting supply and geographic reach of donor hearts, and innovative technologies are emerging to address this issue.…”
mentioning
confidence: 99%